Using data‐driven methods to explore the predictability of surface soil moisture with FLUXNET site data. Issue 23 (13th August 2019) - Pan, Jinjing; Shangguan, Wei; Li, Lu; Yuan, Hua; Zhang, Shupeng; Lu, Xinjie; Wei, Nan; Dai, Yongjiu
Abstract: Soil moisture (SM) is a key variable of land surface‐atmosphere interactions. Data‐driven methods have been used to predict SM, but the predictability of SM has not been well evaluated. This study investigated what variables and methods can be used to better predict SM for leading times of 7 days or longer with a global coverage of FLUXNET site data for the first time. Three machine‐learning models, that is, Bayesian linear regression, random forest, and gradient boosting regression tree, are used for the prediction. Variables including atmospheric forcing, surface soil temperature, time variables (year, day of year, and hour), the Fourier transformation of time variables, and lagged SM (7‐ to 14‐day lagged) were sequentially added into models. A framework with five experiments is designed for factorial exploration of SM predictability. A stepwise method was used to build the best models for each site. The performance of regression models became better when adding more explaining variables in most cases. The results showed that from 50 to 95% of variation of the best models can be explained. The important explaining variables are lagged surface SM, followed by day of year, year, soil temperature, and atmospheric forcing. The predictability of SM depends highly on SM memory characteristics and the persistence of seasonality. The effect of SM memory characteristics on SM prediction as an initial condition question has been widely discussed in this paper. Our results also provide an insight that mechanisms of seasonality effects on SM should be also paid more attention to. Abstract : A framework with five contrasting experiments is designed to investigate the factors affecting the predictability of soil moisture (SM). The best models can explain between 50% and 95% of variation with different explaining variable combinations at different sites. The important explaining variables are lagged surface SM, followed by day of year, year, soil temperature and atmospheric forcing. The predictability of SM depends highly on SM memory characteristics and the persistence of seasonality.